No impact of helminth coinfection in patients with smear positive tuberculosis on immunoglobulin levels using a novel method measuring Mycobacterium tuberculosis-specific antibodies - Giggil Pushpamithran; Camilla Skoglund; Fanny Olsson; Melissa Méndez-Aranda; Thomas Schön; Mårten Segelmark; Olle Stendahl; Robert H. Gilman; Robert Blomgran (Allergy, Asthma & Clinical Immunology, 2023)
Abstract Helminth/tuberculosis (TB)-coinfection can reduce cell-mediated immunity against Mycobacterium tuberculosis (Mtb) and increase disease severity, although the effects are highly helminth species dependent. Mtb have long been ranked as the number one single infectious agent claiming the most lives. The only licensed vaccine for TB (BCG) offers highly variable protection against TB, and almost no protection against transmission of Mtb. In recent few years the identification of naturally occurring antibodies in humans that are protective during Mtb infection has reignited the interest in adaptive humoral immunity against TB and its possible implementation in novel TB vaccine design. The effects of helminth/TB coinfection on the humoral response against Mtb during active pulmonary TB are however still unclear, and specifically the effect by globally prevalent helminth species such as Ascaris lumbricoides, Strongyloides stercoralis, Ancylostoma duodenale, Trichuris trichiura. Plasma samples from smear positive TB patients were used to measure both total and Mtb-specific antibody responses in a Peruvian endemic setting where these helminths are dominating. Mtb-specific antibodies were detected by a novel approach coating ELISA-plates with a Mtb cell-membrane fraction (CDC1551) that contains a broad range of Mtb surface proteins. Compared to controls without helminths or TB, helminth/TB coinfected patients had high levels of Mtb-specific IgG (including an IgG1 and IgG2 subclass response) and IgM, which were similarly increased in TB patients without helminth infection. These data, indicate that helminth/TB coinfected have a sustained humoral response against Mtb at the level of active TB only. More studies on the species-specific impact of helminths on the adaptive humoral response against Mtb using a larger sample size, and in relation to TB disease severity, are needed.